Unique health identifier assessment tool kit. - Roth,Susann (Metro Manila, Philippines Asian Development Bank, 2018)
Unique health identifiers help improve quality and continuum of care, strengthen surveillance of communicable diseases, eradicate diseases, and optimize provider and payer transactions in health financing schemes. They are important enablers for achieving Universal Health Coverage. Through this tool kit, governments and experts will learn how to assess the existing legal, policy, and institutional framework; information and communication technology infrastructure; and current use of identifiers relevant for the health sector, to inform policy decisions on advancing unique identification in the health sector.
Keywords: Health care reform -- Asia; Health services accessibility -- Developing countries; Electronic books